JÓZEFAT ZIELONACKI ZAPOMNIANY POLSKI ROMANISTA XIX W. SZKIC DO BIOGRAFII - Zięba, Agnieszka (Zeszyty Prawnicze, 2017)
Józefat Zielonacki - A Forgotten Polish Romanist of XIX C. An Outline of a Biography Summary J. Zielonacki was born on 28 November 1818 in a village called Goniczki, situated the Grand Duchy of Poznan, which belonged to his family. He spent his childhood in his family estate. After completing education in schools in Trzemeszno and Poznan he studied in Berlin, where he graduated in 1845 and conferred a doctor degree (dr) in both laws. In 1848 (or 1849) he was qualified as an assistant professor (dr hab) at Wroclaw University, where he subsequently lectured the Roman law. In 1850 Prof. Zielonacki succeeded to be a head of the Roman law department at the Jagiellonian University. At that time Galicia was in the period of absolutist reaction after the People’s Spring, distinguished by the suppression of civil liberties and a regime of terror. The declaration of a state of siege on 10.01.1849 led to handing over a full authority to Austrian generals, subsequent military commanders of the country, to whose authority - legitimately and in practice - (in these circumstances) the Galician governor - Agenor hr. Goluchowski was - submitted. The University was in practice deprived of its autonomy; all important matters were meticulously directed and supervised by the central authorities in Vienna. Appointments to professorships depended exclusively on the Austrian Ministry of Education, which also examined in detail ‘the political conformity’ of each candidate. Prof. Zielonacki was put up as a candidate by the minister Leon hr. Thun, who wrote in the application to the Emperor about a “great talent” but also “unblemished political attitude” of the candidate. J. Zielonacki lectured the Roman law in Cracow for two years and a half - until the end of December 1852. He was popular amongst the students and was respected amongst scholars as an eminent expert of the Roman law. On 1.01.1853 - without giving any justification, Prof. Zielonacki was removed from the University together with the following Professors: A. Malecki, W. Pol, A. Z. Helcel. The reasons for the dismissal have not been fully explained; at present it is considered as a revenge of the authorities for “the national attitude of the university full of dignity and visible efforts to maintain the Polish character” or even “acts of terror”. The direct reason for dismissing the “inconvenient” Professors was a denunciation against Prof. Malecki and Prof. Pol (and possibly Kremer), which drew the attention of the police to the whole academic environment. The head of the police in Cracow - Carol Neusser - who was commissioned to check the grounds of the denunciation, invigilated all university professors. It was claimed in his report (written on 21.03.1852) that some of the lecturers were particularly dangerous for the authorities. Prof. Zielonacki was described to be an impulsive person, having - “apart from Polish revolutionary tendencies, plenty of Prussian prejudices against Austria”, behaving “always unfriendly” towards the government. Thus, the removal of the professors had a clear political context - no particular accusations were however formulated. After the dismissal from the Jagiellonian University, Prof. Zielonacki was moved to Innsbruck, where he was the head of the Roman law department (until 1855), and afterwards he took over the same post at the Karol University in Prague. In 1857 Prof. Zielonacki, at his own request, was moved to the Lwow University, where he taught Roman law until he retired in 1870. In 1861 he tried to go back to Cracow to take over a vacant post in the Roman Law department but the authorities rejected his candidacy. Prof. Zielonacki made major contributions to the polonization of the Lwow University - he was the first and - for a long time - the only professor lecturing in Polish. In intense disputes with German professors he managed to win the right to use the Polish legal terminology during the lectures, subsequently a right for lectures in Polish, and afterwards to use Polish during exams. Fighting for the polonization of the university had an impact on his professorship career - after he was elected to be the dean of the Law Faculty for the first time for the academic year 1861/61 - he was ostentatiously neglected by his colleagues in elections to this post. Prof. Zielonacki, apart from his work with students, was also active in other areas: between 1867 and 1873 he was a member of the Autrian State Tribunal, and above all an active member of the Science Academy (from 1873 - since it was established). After Prof. Kramers death, from 1875 to 1878, he was a director of the Philosophy and History Faculty and played a significant role in establishing the Commission of Law in the Science Academy. Prof. Zielonacki died in his family estate in Goniczki on 28.04.1884. His scientific output is very ample - he wrote numerous articles and dissertations (in Latin, German and Polish) mainly on possession and usucaption. He is also an author of two monographs on servitudes (Wroclaw 1849) and on possession (Poznan 1854). The latter was also issued in Polish. The work of his lifetime was a two pans manual “Pandekta, i.e. a lecture on the Roman private law as it is the basis of the new laws” published in Polish in Cracow (1862/63, issue II 1870/1871), dedicated to “Polish youth devoting to the legal profession”. This work was greatly appreciated at his times. At present Prof. Zielonacki is groundlessly forgotten. He belonged to the most eminent Romanists of his times, he was an expen in Latin and German literature on the Roman law. He also substantially contributed to the polonization of law teaching. His personage - as an eminent scholar and patriot - it worth recalling.